Mixture of fatty alcohols and alkyl polyglucosides stabilizing water-in-water emulsions - Dari, Carolina; Si, Yuchen; Douliez, Jean-Paul; Tahon, Jean-François; Benezech, Thierry; Clegg, Paul S.; Fameau, Anne-Laure (Frontiers in Soft Matter, 2023)
The combination of surfactants and fatty alcohols leads to the formation of lamellar gel network (LGNs) which are widely used in cosmetic and pharmaceutical industries. Alkyl polyglucosides (APGs) are known to stabilize oil-in-water emulsions and here, we report their use in combination with fatty alcohol for the stabilization of all-aqueous Water-in-water (W/W) emulsions based on dextranin-poly(ethylene glycol). Two different APGs were used: decyl glucoside and lauryl glucoside. We systematically studied the influence of the concentrations of APGs, and the molar ratio between the APGs and decanol as model fatty alcohol on the size and stability of the aqueous emulsion droplets with time. The self-assembled structure formed by decanol/APGs was characterized by using Small Angle X-ray Scattering and confocal microscopy, and shown to be lamellar in the bulk phase and probably also at the surface of dextran-rich droplets. We also demonstrated that the stabilization of W/W emulsions can be extended to other APG and to other fatty alcohols. In addition, we reported the production of a foam using such W/W emulsions as the continuous phase. Our results show that it is possible to stabilized W/W emulsions using LGNs based on different APGs and fatty alcohols, which will undoubtedly expand the use of W/W emulsions for various fields.